The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1097/sla.0000000000000626
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Perspectives of Care and Surgical Outcomes in Michigan

Abstract: Objective To determine the relationship between postoperative morbidity and mortality and patients' perspectives of care. Summary Background Data Priorities in healthcare quality research are shifting to place greater emphasis on patient-centered outcomes. Whether patients' perspectives of care correlate with surgical outcomes remains unclear. Methods Using data from the Michigan Surgical Quality Collaborative clinical registry (2008–2012), we identified 41,833 patients undergoing major elective general or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
3

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 19 publications
0
32
3
Order By: Relevance
“…This reinforces the idea that patient experience largely reflects the interpersonal elements of care more so than surgical quality. Although a recent study demonstrated a relationship between HCAHPS scores and recommended process use in surgery, other studies have suggested that the link between patient perspective and surgical outcomes remains elusory . This may stem in part from the use of an instrument not tailored specifically to cancer care or surgery.…”
Section: Discussionmentioning
confidence: 99%
“…This reinforces the idea that patient experience largely reflects the interpersonal elements of care more so than surgical quality. Although a recent study demonstrated a relationship between HCAHPS scores and recommended process use in surgery, other studies have suggested that the link between patient perspective and surgical outcomes remains elusory . This may stem in part from the use of an instrument not tailored specifically to cancer care or surgery.…”
Section: Discussionmentioning
confidence: 99%
“…28 In addition, recent studies that examine the relationship of surgical quality metrics to patient satisfaction have used pooled (medical and surgical) HCAHPS data as an outcome variable, a practice which has important limitations. 29,30 Given this information, we plan to examine S-CAHPS results in response to more traditional outcomes measures, such as NSQIP-defined complication rates. The broad application of S-CAHPS to clinical practice if successful will allow much more meaningful outcome data for these and other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Tsai et al 11 also found an association between low risk-adjusted mortality in surgical patients and high satisfaction scores on HCAHPS. However, Sheetz et al 13 in an evaluation of the Michigan Surgical Quality Collaborative registry did not find a significant difference in risk-adjusted mortality between hospitals with high versus low HCAHPS total performance scores (4% mortality in the lowest quintile vs. 3.3% mortality in the highest quintile). Elliott and colleagues, 14 similarly showed no correlation between patient satisfaction and one year mortality.…”
Section: Correlating Hospital Characteristics and Surgical Outcome Mementioning
confidence: 95%
“…Similarly Sheetz et al 13 showed no correlation between risk adjusted complication rates and satisfaction on the HCAHPS survey (25% morbidity in lowest quintile vs 25% morbidity in highest quintile). Gurland and colleagues also found that patients with postoperative complications had no diminution in the overall patient satisfaction ranking domains 18 .…”
Section: Correlating Hospital Characteristics and Surgical Outcome Mementioning
confidence: 95%